Investigating the various properties of cold sprayed CuAlNi shape memory alloys developed by post annealing process. (March 2021) - Sekar, Shiva; Brown, Sam; Cockburn, Andrew; Iyamperumal Anand, Palani; Paul, Christ Prakash; O'Neill, William
CuAlNi shape memory alloy (SMA) has wide scope in vibration damping applications for machine tools. A bespoke cold spray based additive manufacturing system was used to fabricate CuAlNi SMA precursor structures of two different compositions with optimized deposition parameters, which were subsequently alloyed via annealing. The two compositions of CuAlNi chosen for the study were Cu rich in wt% (Cu-82%, Al-14%, Ni-4%) and the Ni rich in wt% (Cu-12%, Al-2%, Ni-80%) shape memory alloy material. The various properties of developed samples were compared with commercially available CuAlNi structure. The properties compared include surface morphology, crystal structure, phase transformation temperature, and mechanical properties were studied with scanning electron microscopy (SEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC) compression testing respectively. The shape memory characteristics were also analyzed using dynamic mechanical analyzer (DMA). Among the two samples, Cu rich sample exhibited better SMA qualities than Ni rich sample as reported in the literature. The micro-hardness of Cu rich sample was to be 356 ± 3 VHN comparatively lower than Ni rich sample. The DSC results revealed the phase transformation hysteresis for Cu rich sample to be very low at 5 ± 3°C. The Cu rich CuAlNi SMA showed very good shape memory characteristics in the DMA results in the range of 50°C to 100°C.